Immune profiling of ART-conceived children in Kazakhstan: a case-control study - Ilmuratova, Sevara; Lokshin, Vyacheslav; Prodeus, Andrey; Manzhuova, Lyazzat; Nurgaliyeva, Zhanar; Kussainova, Farida; Bazarbaeva, Aygul; Nekhorosheva, Valeriya; Abshekenova, Aygerim (Frontiers in Pediatrics, 2024)
Objective: The increasing use of assisted reproductive technologies (ART) has led to a growing interest in the health outcomes of offspring. However, the impact of ART on the immune system of children remains poorly understood. While only two publications were found, their findings contradict each other and did not consider other risk factors in their analysis except for ART use. Therefore, this study aimed to examine the potential impact of ART on the immune system of offspring. Methods: A case-control study was conducted in Kazakhstan to investigate the immune system of ART-conceived children compared to those conceived naturally (NC). The study included participants who met certain criteria, such as having undergone a successful ART program resulting in the birth of either a single or multiple pregnancies. Patients who used donor oocytes/sperm, intrauterine insemination, or surrogacy were excluded. Anamnesis data were collected from children in both groups, and laboratory measurements were performed and analyzed using IBM SPSS Statistic 26. Results: A total of 120 children conceived by ART and 132 NC children under the age of five were included in our study. We observed that compared with NC group, ART children had lower IgA and IgG levels (p<0.001), absolute lymphocytosis, high levels of active T-lymphocytes (p=0.001), and pathological T-helper levels (p=0.004). Therefore, the clinical presentation of respiratory diseases was lower in ART group. Children born after frozen embryo transfers showed significantly higher levels of T-cytotoxic and active T-lymphocytes compared to children born after fresh embryo transfers (p=0.007 and p=0.020, respectively). We utilized ordinal logistic regression to control for confounding variables such as multiple pregnancy, cesarean section, premature birth, and breastfeeding. Despite this, the significant impact of ART on immunogram parameters persisted, indicating the independent and influential nature of ART or other unaccounted factors.